2022
DOI: 10.4103/ijd.ijd_671_21
|View full text |Cite
|
Sign up to set email alerts
|

Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis

Abstract: Background: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute, life-threatening, severe drug reactions. Randomized studies on these diseases are difficult to perform. Aims and Objectives: The purpose of this study was to summarize the demographic and clinical characteristics of patients with SJS and TEN in a tertiary hospital in Turkey. Materials and Methods: We evaluated the records of 33 patients with SJS and TEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…There is a certain gender difference in SJS/TEN patients. Most previous studies showed a female predominance, 14 21 consistent with the present study, but there were still a few literatures to show that males are more susceptible than females. 22 Some researchers found that female patients had worse prognosis and higher mortality, 23 but we did not find a correlation between gender and death.…”
Section: Discussionsupporting
confidence: 92%
“…There is a certain gender difference in SJS/TEN patients. Most previous studies showed a female predominance, 14 21 consistent with the present study, but there were still a few literatures to show that males are more susceptible than females. 22 Some researchers found that female patients had worse prognosis and higher mortality, 23 but we did not find a correlation between gender and death.…”
Section: Discussionsupporting
confidence: 92%
“…Dentre as associações de fármacos com SSJ/NET, as evidências apontam, de modo geral, os antibióticos como causadores mais comuns, mas, além deles, estão em destaque alopurinol (inibidor enzimático), carbamazepina (anticonvulsivante), lamotrigina (anticonvulsivante), AINEs com oxicam, nevirapina (antirretroviral) e sulfassalazina (antiinflamatório) (Acar et al, 2022). Geralmente, o intervalo entre exposição medicamentosa e início da SSJ/NET é de 4 a 28 dias e inclui lesões cutâneas vistas como máculas vermelho-escuras e sintomas prodrômicos, como dor de garganta e queimação nos olhos; além disso, a dor na pele é um achado de alerta para necrose epidérmica (Acar et al, 2022).…”
Section: Associação Entre Ssj/net E Antibióticosunclassified
“…Stevens-Johnson syndrome/toxic epidermal necrolysis is the most dreaded adverse cutaneous drug reaction and is potentially fatal, if not promptly managed. 1 It is reported with medications such as non-steroidal anti-inflammatory drugs, anticonvulsants, antibiotics (beta-lactam), allopurinol and barbiturates; immune checkpoint inhibitors can also result in Stevens-Johnson syndrome/toxic epidermal necrolysis uncommonly. Pembrolizumab is a highly selective humanised monoclonal IgG4 antibody, directed against the programmed cell death-1 protein receptor on the cell surface.…”
Section: Sirmentioning
confidence: 99%